THE ROLE OF PRINCIPAL SUPERVISION, EDUCATION AND TRAINING, AND THE IMPROVEMENT OF TEACHER PROFESSIONALISM AT UPTD SMP NEGERI 2 SEKAMPUNG UDIK, EAST LAMPUNG REGENCY - Raminto, Raminto; Khairudin, Khairudin; Rahayu, Ni Putu Widhia (Program Studi Magister Manajemen, 2024)
This study aims to explore the role of principal supervision, education, and training in enhancing teacher professionalism at UPTD SMP Negeri 2 Sekampung Udik, East Lampung Regency. The objectives are to (1) analyze the effectiveness of school principal supervision in improving teacher professionalism, (2) evaluate the implementation of education and training programs, and (3) identify the supporting and inhibiting factors affecting professional development. The research employed a qualitative method using observation, interviews, and documentation as data collection techniques. Data were analyzed using the interactive analysis model consisting of data reduction, data display, and conclusion drawing. The results show that principal supervision has been implemented effectively through planning, execution, and evaluation stages. Education and training programs were found to be beneficial in enhancing professionalism, as evidenced by structured training needs analysis, curriculum development, implementation, and evaluation. Supporting factors include teacher discipline, motivation, and rewards, while inhibiting factors involve limited educational funding and lack of attention to teacher development.